(untitled) (Journal of Economic Research & Business Administration, 2015)
Article is devoted to justification of need of development of new scientific approach to an assessment of poverty and a statement of author’s suggestions for improvement of methodology of an assessment of poverty and problems of the Kazakhstan economic strategy of social modernization